(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The theme of love as resistance to authority is the centerpiece of a two-millennia-long tradition in Western poetry known as carpe diem (a phrase credited to the Latin poet Horace). This essay begins by analyzing one of the most famous later examples of carpe diem in English poetry (Andrew Marvell’s 1681 “To His Coy Mistress”), emphasizing the carpe diem ethos’ potential to illustrate both the consequences and the necessity of individual erotic choice—especially female choice—in defiance of authority. It then uses carpe diem’s anti-authoritarian perspective to understand the contrast between the ambivalence of Mariam—torn between a tepid disobedience and regretful loyalty to her husband Herod—and the wholly defiant choices of Salome in Elizabeth Cary’s earlier drama, The Tragedy of Mariam from 1613.